FAKTOR-FAKTOR YANG MEMENGARUHI KEGAGALAN IBU DALAM MEMBERIKAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN - Nur Hidayati (Oksitosin : Jurnal Ilmiah Kebidanan, 2016)
The failure of breastfeeding is not good conditions for growth and development of infants in which breastfeeding is very important nutrition for infants before the age of 0-6 months. This study aims was to analyze the relationship between level of understanding, working status, culture, sore nipples, breast swelling and existing breastfeeding mothers to failure in exclusive breastfeeding in infants aged 0-6 months.This study was observational analytic study design analytic comparison with a sample of mothers who have children ages 0-6 who have faile obtained d to feed that exclusive breastfeeding in the inverse bulk village, district Situbondo. The sample size is 41 people. Data were collected by means of a survey using a questionnaire that had been tested its validity and observation sheet. data were tested using the chi square (X ²).In this study it was found that there was an effect of understanding the factors (p = 0.007), cultural p = 0.007), working mothers (p = 0.0010), sore nipples (p = 0.001), expenditure breastfeeding (p = 0.0029) and breast swelling (p = 0.004).There factors that affect maternal failure in exclusive breastfeeding in infants aged 0-6 months. Keywords: Understanding, working mothers, social cultural, sore nipples, breast swelling, breastfeeding expenditure. ABSTRAK Kegagalan pemberian ASI merupakan kondisi tidak baik untuk tumbuh kembang Bayi dimana ASI merupakan asupan gizi yang sangat penting untuk Bayi sebelum usia 0-6 bulan. Penelitian ini bertujuan untuk menganalisa adanya hubungan antara factor-fakor yang mempengaruhi kegagalan ibu dalam memberikan ASI Eksklusif pada Bayi usia 0-6 bulan. Penelitian ini adalah penelitian observasional analitik dengan desain analitik komparasi dengan sampel ibu yang memiliki Bayi usia 0-6 yang gagal memberikan ASI eksklusif di Desa Curah Kalak, Kabupaten Situbondo. Besar sampel yaitu 41 orang. Pengambilan data dilakukan dengan cara survey menggunakan kuesioner dan lembar observasi. Data yang diperoleh diuji menggunakan chi kuadrat (x²). Pada penelitian ini didapatkan bahwa ada berpengaruh antara faktor pemahaman (p=0,007), budaya p=0,007), ibu bekerja (p=0,0010), puting susu lecet (p=0,001),pengeluran ASI (p=0,0029) dan payudara bengkak (p=0,004) dengan kegagalan ibu dalam memberikan ASI Eksklusif pada Bayi usia 0-6 bulan. Kata kunci: Pemahaman, ibu bekerja, sosial budaya, puting susu lecet, payudara bengkak, pengeluaran ASI.